Malnutrition, Prevalence and Relation to Some Risk Factors among Elderly Residents of Nursing Homes in Tehran, Iran - Lyly Nazemi; Ingmar Skoog; Ingvar Karlsson; Saeed Hosseini; Mohammad Reza Mohammadi; Mostafa Hosseini; Mohammad Javad Hosseinzade; Seyed Alireza Mesbah-Namin; Masoud Baikpour (Tehran University of Medical Sciences, 2015)
Background: Malnutrition and dehydration are two most common types of ailments residents of nursing homes (NH) prone to. It is very important to assess these problems because they can predispose the residents to severe illnesses. The aim of this study was to gather information on nutritional status and its associated risk factors in elderly residents of NHs in Tehran, Iran. Methods: From 16 NHs in Tehran, 263 residents were randomly selected. Data were collected via questionnaires, including demographic characteristics, past medical history, present health problems and daily routines. The MNA questionnaire was used to gather information regarding their nutritional status. Results: The present study showed that 10.3% of the elderly residents in nursing homes were malnourished. 66.4% of males and 70.8% of females were at risk of malnutrition. Multivariate analysis showed that after adjusting for confounders the following elderly-related factors were the independent risk factors of malnutrition: consuming half or less than of the food (OR=8.0, 95%CI=3.7-17.7), having no teeth or good prosthesis (OR=1.7, 95%CI=1.1-2.7), diabetes (OR=1.6, 95%CI=1.1-2.4), smoking (OR=0.6, 95%CI=0.3-1.2), studying (OR=0.4 95%CI=0.2-0.9) and praying in their free time (OR=1.8 95%CI=1.2-2.6). Conclusion: The subjects' health-related factors and their free-time activities and nutritional behavior are the most important factors associated with poor nutrition among elderly residents of NHs; however, further investigation is needed to clarify the role of other factors in maintaining a suitable nutritional plan for them.